Association between obesity and fracture risk in Chinese women above 50 years of age: a prospective cohort study - Hui Li; Qunying Xu; Yunli Ye; Bei Chang; Rui Wang; Guangwen Li (BMC, 2024)
Abstract Background Fractures present serious health challenges for older adults, including premature mortality and reduced quality of life. Obesity has become significantly prevalent in China. However, the association between obesity and fractures remains unclear. This study aimed to assess the association between obesity and fractures among Chinese women above 50 years of age. Methods A prospective cohort study was designed based on the China Health and Nutrition Survey, using data from 1997 to 2015. The average follow-up duration was seven years. Trained investigators measured body mass index (BMI) and waist circumference (WC) at baseline. Obesity was defined according to World Health Organization recommendations. Waist-to-height ratio (W-HtR) was calculated, with 0.5 as the cutoff value. Onset of fractures, self-reported by the participants during the follow-up period, was the primary outcome. Cox hazard regression models were used to assess the association between BMI, WC, W-HtR and subsequent risk of fracture. A sensitivity analysis was conducted by multiple imputation of missing data on the variables at baseline. Results A total of 2,641 women aged ≥ 50 years were involved in the study. In all the models, no significant association existed between BMI and fracture risk. However, women with WC ≥ 88 cm had significantly higher risk of fracture than those with WC < 80 cm according to both the unadjusted (HR = 1.744, 95% CI: 1.173-2.591) and adjusted models (HR = 1.796, 95% CI: 1.196-2.695). In addition, W-HtR and fracture risk were positively associated according to both the unadjusted (HR = 1.798, 95% CI: 1.230-2.627) and adjusted models (HR = 1.772, 95% CI: 1.209-2.599). Results of the sensitivity analysis were consistent with those of the above analyses. Conclusions Abdominal obesity increased the risk of all-cause fractures in Chinese women ≥ 50 years old. Intervention strategies and measures to prevent or address abdominal obesity would be helpful to decrease the fracture incidence.